Ebenezer Sprout and William Shepard orderly book - Sprout, Ebenezer, -1805.; Shepard, William, 1737-1817.
Handwritten bound transcript of an orderly book (151 pages) containing general, brigade, and regimental orders (1780 January 17-February 13), emanating from various camps in New York state, received by Lt. Col. Ebenezer Sprout, 12th Massachusetts Regiment. Also includes orders (1779 August 30- 1780 January 16) of Col. William Shepard, Fourth Massachusetts Regiment.
Microfilm edition available
Handwritten transcript.
Microfilm produced from transcript in the Manuscript Division.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Army. -- Massachusetts Regiment, 12th.; United States. -- Continental Army. -- Massachusetts Regiment, Fourth; United States. -- Continental Army -- Order-books.; Massachusetts -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers